Implementasi Landasan Hukum Pada Pendidikan Inklusi - Syarifah Robiyah; Atifatul Atiqoh; Hamidah Rizki Ardhani; Opi Andriani (JURNAL ILMIAH RESEARCH STUDENT, 2024)
The aim of this research is to determine the application of the legal basis for inclusive education for children with special needs. The method used in this study is a literature review study or literature review. Literature study is a research design used in collecting data sources related to a topic found in the field. Data collection for literature studies was carried out using the Google Scholar search tool. The results of appropriate and required screening, there are 5 National Journal articles based on the articles found and analyzed. The results of this research found that the application of the legal basis for inclusive education for children with needs has been implemented well.